Linguagem e resistência: Trajetória do discurso feminino na luta contra a opressão (Mulheres no Discurso - Women in Discourse, 2025)
The history of thought in Western Europe has shaped our perception of human differences through simplistic oppositions: good versus evil; dominant versus subordinate. However, the foundations of such classifications are not explicitly defined, allowing the very system to reinforce the distinctions it has created. As a result, certain groups — notably Black people and especially women — are systematically marginalized, regarded as dispensable in relation to ideals of profit and power in their various forms. This process of oppression often leads the oppressed group to adopt the language and behavior of their oppressors in an unconscious attempt at survival or illusory protection. Audre Lorde questions: “Whenever the need for some kind of communication arises, those who fight against our oppression invite us to share our knowledge with them” (Lorde, 2019, p. 239). Building on this question, this study aims to explore how women — whose bodies, intellect, and lives are stigmatized — have claimed a new social space through language, particularly at the turn of the twentieth to the twenty-first century. We will trace an analytical path from the texts of Simone de Beauvoir (The Second Sex, 1949) to the contemporary contributions of Judith Butler (Gender Trouble, 1990), Sueli Carneiro (Racism, Sexism and Inequality in Brazil, 2003), and Gayatri Spivak (Can the Subaltern Speak?, 1988). Our objective is to examine the evolution of the debate on the role of women in discourse and, through a dialectical approach inspired by cultural studies, to discuss how these thinkers were themselves shaped by their historical contexts and whether the debates and linguistic strategies remain the same. The adopted methodology will be criticaltextual analysis. We will engage in close readings of an essay or representative excerpt from each author’s work, focusing on the linguistic and rhetorical mechanisms that underpin their arguments. The analysis will also consider contextual elements (time, place, intellectual trajectory) to understand the singularities of each theoretical production and its connections with specific political struggles. This examination will allow us to identify the linguistic and discursive mechanisms used to challenge the status quo and to promote an effective claim to female knowledge. This project seeks to offer significant contributions to the understanding of the dynamics of female discourse and to reveal both advances and ongoing challenges in thestruggle against the aforementioned systemic oppression.